Going to a beach - Rissman, Rebecca (Chicago, Ill Heinemann Library, 2012)
Describes what different beach shores can be made of, including black or white sand, rocks, and pebbles
Games
1 2 13
Keywords: Beaches -- Juvenile literature; School field trips